2012
DOI: 10.1074/jbc.m112.406389
|View full text |Cite
|
Sign up to set email alerts
|

GCN5 Protects Vertebrate Cells against UV-irradiation via Controlling Gene Expression of DNA Polymerase η

Abstract: Background: DNA polymerase (POLH) whose deficiency is responsible for XPV is essential for translesion DNA synthesis. Results: GCN5-deficiency in DT40 causes both enhanced sensitivity to UV-irradiation and down-regulation of POLH expression. Conclusion: GCN5 protects cells against UV-irradiation via controlling POLH gene expression.Significance: This is the first study that reveals involvement of GCN5 in UV-tolerance through transcription activation of POLH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
28
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 37 publications
4
28
0
Order By: Relevance
“…Generations of ∆GCN5 and human POLH (hPOLH)-overexpressing ∆GCN5 were described in our previous reports (Kikuchi et al, 2005;Kikuchi et al, 2012). DT40 cells and all subclones were cultured essentially as described (Kikuchi et al, 2005).…”
Section: Cell Culture and Treatments With 4nqomentioning
confidence: 99%
See 1 more Smart Citation
“…Generations of ∆GCN5 and human POLH (hPOLH)-overexpressing ∆GCN5 were described in our previous reports (Kikuchi et al, 2005;Kikuchi et al, 2012). DT40 cells and all subclones were cultured essentially as described (Kikuchi et al, 2005).…”
Section: Cell Culture and Treatments With 4nqomentioning
confidence: 99%
“…Studies using ∆GCN5 revealed that GCN5 participates in cell cycle progression at G1/S phase transition (Kikuchi et al, 2005), B cell receptor-mediated apoptosis signaling (Kikuchi and Nakayama, 2008), phosphatidylinositol 3-kinase (PI3K)/Akt survival pathway (Kikuchi et al, 2011a), superoxide-generating system (Kikuchi et al, 2011b), B cell development (Kikuchi et al, 2014a), immunoglobulin heavy chain gene expression (Kikuchi et al, 2014b), protein kinase Cθ gene expression (Kikuchi et al, 2014c) and endoplasmic reticulum stress-induced apoptosis (Kikuchi et al, 2015). In particular, interestingly, GCN5 protects cells from UV-irradiation via controlling DNA polymerase η (POLH) gene expression whose deficiency is responsible for XP variant (XPV) (Kikuchi et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…RT-PCR was carried out essentially as described [11,12,16,17,[20][21][22]. PCRs were carried out using chicken PKCs primers listed in the previous report [12].…”
Section: Semiquantitative Reverse Transcription-polymerase Chain Reacmentioning
confidence: 99%
“…ChIP assay was performed using Chromatin Immunoprecipitation Assay Kit (Millipore, Billerica, MA, USA) as described [20][21][22][23]. Immunoprecipitation with anti-GCN5 antibody (Chemicon, Temecula, CA, USA), anti-acetylated histone antisera (Millipore) or anti-Flag M2 antibody (Sigma-Aldrich, St. Louis, MO, USA) was carried out.…”
Section: Chip Assaymentioning
confidence: 99%
See 1 more Smart Citation